Design of Dual-Head 3D Printer - Chalupa, Vlastimil; Stanek, Michal; Vanek, Jiří; Strnad, Jan; Ovsik, Martin (Manufacturing Technology Journal, 2023)
Fused Filament Fabrication (FFF) printers are usually designed to create a product with one single ma-terial. Some of them allow fabricate items in multiple colours but creating a single product consisting of two different materials remains an advantage of industrial 3D printers only. The aim of this research was to develop a design of a device with two printheads which enables to print products with two different materials, compatible with a cheap and commonly available FFF device Prusa i3MK2S, and the subse-quent production of a prototype. A key aspect of the design was the hardware compatibility of the device with the given printer while maintaining the maximum possible printing area.
Keywords: dual extrusion; mulit-material 3D print; FFF printer